Pandemic Metaphors, Posthuman Futures, and the Ethics of AI in Literature (Journal of Informatics Education and Research, 2025)
Pandemics have long offered fertile ground for literary metaphor—plague as punishment, as existential dread, as inevitable collapse. Yet the twenty-first century demands a different reckoning. As artificial intelligence, surveillance technologies, and biotechnology reshape human life at its roots, the metaphors through which pandemics are understood and narrated must also evolve—or risk becoming quaint relics, mere echoes of past fears. This paper examines the historical evolution of pandemic metaphors from Boccaccio and Defoe through Camus and García Márquez, tracing how disease has mirrored moral, social, and philosophical anxieties across centuries. It argues that in our current era, the true contagion is no longer solely biological but informational, algorithmic, environmental. Through close readings and theoretical reflection, this study explores how contemporary and future literature must respond: crafting metaphors that grapple not only with death and suffering, but with the erasures of human agency by AI systems, the surveillance of bodies and behaviors, and the uneasy hybridization of biology and code. In doing so, it insists that literature’s ethical mission is not diminished but intensified. Pandemic literature must resist not only the virus but the viral logic of a world increasingly scripted by machines. To survive as a meaningful cultural form, it must forge new metaphors for a future where “plague” may arrive as a data breach, a bioengineered accident, or a loss of narrative itself.